Rebecca and Ana - Greene, Jacqueline Dembar (American Girl Pub., 2009)
Nine-year-old Rebecca Rubin eagerly helps her cousin Ana, newly arrived from Russia, to adjust to life in New York City, but when their teacher says the two must sing together at a school assembly, Rebecca worries that her big moment will be ruined.